Computer tomography (CT) scans as a diagnostic tool for interpretation of S10 plastinated slides from dog cadaver - Pendovski Lazo, Bozhinovski Dimitar, Ilievska Ksenija, Trojachanec Plamen, Ilieski Vlatko (My University, 2022)
Computed tomography (CT) is a routine method for the diagnosis of pathological structures in the body and has been widely used in veterinary medicine as an advanced diagnostic imagining tool in veterinary clinics. However, interpretation of CT scans requires detailed knowledge of topographical animal anatomy and usually has limited scan resolution due to the ambiguous relationship between signal intensity and tissue composition. The aim of the study was to assess the morphometric similarities between S10 plastinated slides and computer tomography (CT) scans and their usability as compatible paired diagnostic methods. A 3-year-old euthanized dog cadaver was scanned on SHIMADZU SCT/6800TXL scanner immediately post-mortem, then frozen at -80 °C to preserve the correct anatomical position, and plastinated with a standardized procedure. Semi-transparent transversal slices (5 mm) were obtained from the head, thoracic, and lumbar sections of the body. The S10 plastinated slides and CT scans contained fine and small anatomical structures with high similarity. The spatial relationships of all anatomical structures on the serial S10 platinates were in the correct anatomical position. In conclusion, S10 transversal slices showed high similarity with the CT scans and allowed identification of the corresponding morphological structures. The S10 thin plastinated transversal slices could be used for additional interpretation of CT transversal scans at veterinary clinics and as a didactical tool for veterinary students.
Keywords: S10 plastination, computer tomography (CT), topographic anatomy, dog